2005
DOI: 10.1088/0031-9155/50/24/014
|View full text |Cite
|
Sign up to set email alerts
|

Thresholding in PET images of static and moving targets

Abstract: Continued therapeutic gain in the treatment of non-small-cell lung cancer (NSCLC) will depend upon our ability to escalate the dose to the primary tumour while minimizing normal tissue toxicity. Both these objectives are facilitated by the accurate definition of a target volume that is as small as possible. To this end, both tumour immobilizations via deep inspiratory breath-hold, along with positron emission tomography (PET), have emerged as two promising approaches. Though PET is an excellent means of defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…At present, various methods are used in practice to delineate PET-based target volumes [16][17][18][19][20][21][22][23][24][25]. The manual delineation of target volumes using different window level settings and look up tables is the most common and widely used technique in the clinic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, various methods are used in practice to delineate PET-based target volumes [16][17][18][19][20][21][22][23][24][25]. The manual delineation of target volumes using different window level settings and look up tables is the most common and widely used technique in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…The manual delineation of target volumes using different window level settings and look up tables is the most common and widely used technique in the clinic. However, the method is highly operator-dependent and is subject to high variability between operators [20,26]. Semiautomated or fully automated delineation techniques might offer several advantages over manual techniques by reducing operator error/subjectivity, thereby improving reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many clinical and phantom studies on appropriate threshold values for PET images [21][22][23][24][25][26][27][28][29][30][31][32] (Table 1). Erdi et al [21] reported that 36%-44% of the maximum FDG activity was appropriate for delineating target volumes larger than 4 ml in a static phantom study.…”
Section: Introductionmentioning
confidence: 99%
“…A priori, it is therefore unlikely that a universal segmentation threshold would match nongated 18 F-FDG PET and non-breathhold CT GTVs in tumors of differing shapes and sizes. The findings of Biehl et al highlight the difficulty in defining a universal threshold as suggested by phantom studies (5).…”
Section: To the Editormentioning
confidence: 96%